1982
DOI: 10.1021/ja00366a004
|View full text |Cite
|
Sign up to set email alerts
|

Chiral discrimination in the monolayer packing of N-(.alpha.-methylbenzyl)stearamides on aqueous acid subphases: thermodynamic behavior

Abstract: The study of monolayers at the air-liquid interface offers unusual opportunities to investigate the effects of stereochemical factors in organized systems. As a first step toward developing this field, we have examined some surface properties of 7V-(a-methylbenzyl)stearamide, comparing the behavior of monolayer films of its racemic modification with its two enantiomeric forms and also with the achiral position isomer TV-phenethylstearamide. X-ray powder diffraction patterns showed that the racemic material was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…14 It has been predicted that 2D chiral resolution on a surface should occur more easily than in three-dimensional crystals. 15 Due to confinement in the plane, certain symmetry elements, like the center of inversion or the glide plane parallel to the surface, are precluded, and enhanced chiral interactions are therefore expected. 16 However, the balance between the molecule-substrate interaction and the lateral intermolecular interactions determines the nature of self-assembly 17 and thus the outcome of lateral resolution.…”
Section: Introductionmentioning
confidence: 99%
“…14 It has been predicted that 2D chiral resolution on a surface should occur more easily than in three-dimensional crystals. 15 Due to confinement in the plane, certain symmetry elements, like the center of inversion or the glide plane parallel to the surface, are precluded, and enhanced chiral interactions are therefore expected. 16 However, the balance between the molecule-substrate interaction and the lateral intermolecular interactions determines the nature of self-assembly 17 and thus the outcome of lateral resolution.…”
Section: Introductionmentioning
confidence: 99%
“…There are often severe complications from medium effects,' despite preliminary indications that medium effects could be ignored.lgb It has also been reported that samples underwent considerable heating during the 1-2 h required for data collection. 20 We observed a gradual and substantial increase in frequency differences between signals for a-and P-carbon atoms for ethyl mesylate (Table 7), which we cannot relate to extent of protonation.…”
Section: Discussionmentioning
confidence: 60%
“…4 In the investigation of monolayers of N-(1-phenylethyl)stearamide by equilibrium spreading pressure and static surface pressure, it was found that the molecules of the homochiral samples were more strongly associated than those of the racemates. 5 Differences in the intermolecular packing of homochiral compared with racemic amphiphiles yielded the spontaneous segregation of enantiomers from racemic mixtures in monolayers of N-dodecylmannonamide and of some hydrophobic amino acids; this was nicely observed by Brewster angle microscopy 6 and grazing incidence X-ray diffraction experiments, respectively. 7 Note that it was proposed that the spontaneous segregation of enantiomers from a racemic mixture in monolayer aggregates might have played an important role in the transformation from racemic chemistry to chiral biology.…”
Section: Biographical Sketchesmentioning
confidence: 92%
“…A number of investigations have focused on this facet of biological membranes and have pointed out, through different models, some consequences of lipid chirality. [4][5][6][7][8][9][10][11][12][13][14][15][16] It was found that the chiral information embedded in the molecular structure of monomers affects the organization of amphiphile aggregates. In fact, the transition temperature (T c ) of homochiral vesicles of 2-methyldodecanoic acid was found to be lower compared with the T c of the racemic vesicles; therefore, at 10 °C, racemic vesicles destabilized causing phase separation, whereas homochiral vesicles remained stable.…”
Section: Biographical Sketchesmentioning
confidence: 99%